Penerapan Terapi Bermain Bola Untuk Mengurangi Kecemasan Pada Anak Dengan Masa Hospitalisasi - Rahma Nur Habibah; Falasifah Ani Yuniarti; Dewi Respati Arumsari (Lembaga Pengembangan Kinerja Dosen, 2023)
Hospitalization is a process that requires children to undergo treatment and therapy at the hospital until they return home. The impact of hospitalization that is most often experienced by children is anxiety. Anxiety experienced by children during hospitalization can be overcome by playing therapy. The purpose of this study was to determine the effect of giving playing ball therapy to hospitalized children with anxiety before examining vital signs. This research method is a descriptive study, with a sample of 2 people in the Hospital of Temanggung Regency. The instrument used to measure anxiety levels is the Spence Children's Anxiety Scale (SCAS). Respondents were given play therapy 3 times in 3 days. The results of this study indicate that the anxiety level of hospitalized children decreased from an average score of 36, namely the moderate anxiety category, to an average score of 20, mild anxiety category.